Efektifitas Pembiasaan Shalat Dhuha Dalam Meningkatkan Karakter Religius Siswa di SMP Muhammadiyah 4 Kebomas - Nisaurrohmah, Hanifah; Amirudin, Noor (Intiqad: Jurnal Agama dan Pendidikan Islam, 2024)
The practice of Dhuha prayer in schools is an effort to shape students' good character. However, it is questionable whether this practice will truly impact students. Therefore, this research, conducted at SMP Muhammadiyah 4 Kebomas, aims to determine and analyze: (a) How Dhuha prayer is implemented at SMP Muhammadiyah 4 Kebomas (b) Whether students at SMP Muhammadiyah 4 Kebomas understand the essence of Dhuha prayer (c) The extent of the influence of Dhuha prayer practice in shaping the religious character of students at SMP Muhammadiyah 4 Kebomas. The approach used in this research is quantitative, with the aid of SPSS 22 software. The research findings indicate that the practice of Dhuha prayer has a relationship in enhancing the religious character of students at SMP Muhammadiyah 4 Kebomas, with a Pearson Correlation of (0.547) r table (0.413). This represents a 30% success rate, meaning the remaining 70% is influenced by other factors. Therefore, the more frequent the practice of Dhuha prayer, the better the students' religious character. However, to shape character optimally, support from various parties, especially parents and the community, is needed. This Study proves that there is a positive influence of habit of dhuha prayer on students’ religious character. Further research also needs to examine other factors that influence the effectiveness of the habit of dhuha prayer in improving students’ religious character.